This discussion is closed.
Meander
Badges:
#1
Report 17 years ago
#1
The sixth term of an arithmetic sequence is equal to twice the the fourth term, and the tenth term equals 48. find the first term "a" and the common difference "d":

here goes:
6th term = 2 * (4th term)
4th term = a + 3d
6th term = 2 (a + 3d)
so, 6th term = 2a + 6d

10th term = a + 9d = 48

help!! i got to this part. i was thinking to simultaneously solve the 2 equations to find "a" and "d", but i dont have an actual value for the 6th term. i only know that the 10 term is 48. please help someone!!
0
theone
Badges: 0
Rep:
?
#2
Report 17 years ago
#2
(Original post by Meander)
The sixth term of an arithmetic sequence is equal to twice the the fourth term, and the tenth term equals 48. find the first term "a" and the common difference "d":

here goes:
6th term = 2 * (4th term)
4th term = a + 3d
6th term = 2 (a + 3d)
so, 6th term = 2a + 6d

10th term = a + 9d = 48

help!! i got to this part. i was thinking to simultaneously solve the 2 equations to find "a" and "d", but i dont have an actual value for the 6th term. i only know that the 10 term is 48. please help someone!!
The 6th term is a+5d.
0
Meander
Badges:
#3
Report 17 years ago
#3
lol..........ohh my god i am so thick. how on earth did i make such a mistake. well, i am really stuck now, please can someone help!!!
0
Juwel
Badges: 18
Rep:
?
#4
Report 17 years ago
#4
(Original post by theone)
The 6th term is a+5d.
Why 5d?
0
theone
Badges: 0
Rep:
?
#5
Report 17 years ago
#5
(Original post by ZJuwelH)
Why 5d?
Because it's the 6th term.
0
theone
Badges: 0
Rep:
?
#6
Report 17 years ago
#6
(Original post by Meander)
lol..........ohh my god i am so thick. how on earth did i make such a mistake. well, i am really stuck now, please can someone help!!!
a+5d = 2a + 6d. So a+d = 0.
0
Juwel
Badges: 18
Rep:
?
#7
Report 17 years ago
#7
(Original post by theone)
Because it's the 6th term.
Oh yeah. Been a while.
0
Juwel
Badges: 18
Rep:
?
#8
Report 17 years ago
#8
(Original post by theone)
a+5d = 2a + 6d. So a+d = 0.
So a=-d and a+9d = 48 so 8d=48 >>> d=6 and go from there.
That right theone?
0
gayboy09
Badges: 0
Rep:
?
#9
Report 17 years ago
#9
I don't know if this is right, if it is, I am Jesus

a+3d = 2a+6d

0=a+3d
48=a+9d

6d=48 d =8

a+ 9(8) = 48
a+72 = 48
a=48-72 = -24

test - a+3d =2a + 6d
-24 + 24 = -48 + 48
0 = 0 its correctamundo
0
theone
Badges: 0
Rep:
?
#10
Report 17 years ago
#10
(Original post by gayboy09)
I don't know if this is right, if it is, I am Jesus

a+3d = 2a+6d

0=a+3d
48=a+9d

6d=48 d =8

a+ 9(8) = 48
a+72 = 48
a=48-72 = -24

test - a+3d =2a + 6d
-24 + 24 = -48 + 48
0 = 0 its correctamundo
The first line is wrong
0
gayboy09
Badges: 0
Rep:
?
#11
Report 17 years ago
#11
On this instant you should ignore gayboy09, his maths is as rusty as a nail that is rusty.
0
Juwel
Badges: 18
Rep:
?
#12
Report 17 years ago
#12
(Original post by gayboy09)
On this instant you should ignore gayboy09, his maths is as rusty as a nail that is rusty.
... Just on this instant?
0
meander
Badges:
#13
Report 17 years ago
#13
ahhh, i see it. we find two expressions for the 4th and 6 th term, we then cancel this to give us an equation. we tthen use this equation and solve it simultaneoulsy with: 10 term = a + 9d = 48 to find a and d:

a + d = 0
a + 9d = 48

-8d = 48
d = 48/(-8)
d = -6

sub d=-6 back into a+d = 0:

a + (-6) = 0
so a = 6

therefore the first term ("a") = 6
the common difference = -6

hooray!!!!!!!
0
Meander
Badges:
#14
Report 17 years ago
#14
where on earth did you guys get d = 8 from? you are using the wrong equation, you are using a + d =0. where did this 3d come from? i got the right answer coz my answer sheet says so. you did it wrong some of you guys
0
Juwel
Badges: 18
Rep:
?
#15
Report 17 years ago
#15
(Original post by meander)
ahhh, i see it. we find two expressions for the 4th and 6 th term, we then cancel this to give us an equation. we tthen use this equation and solve it simultaneoulsy with: 10 term = a + 9d = 48 to find a and d:

a + d = 0
a + 9d = 48

-8d = 48
d = 48/(-8)
d = -6

sub d=-6 back into a+d = 0:

a + (-6) = 0
so a = 6

therefore the first term ("a") = 6
the common difference = -6

hooray!!!!!!!
Actually -8d=-48, so d=6 and a=-6.
0
Meander
Badges:
#16
Report 17 years ago
#16
lol, oops tes, i was rushing a bit there. when i did the question on paper i did it correctly as you said...........i just typed it too fast...
0
Juwel
Badges: 18
Rep:
?
#17
Report 17 years ago
#17
(Original post by Meander)
lol, oops tes, i was rushing a bit there. when i did the question on paper i did it correctly as you said...........i just typed it too fast...
<thumbs up> We got there at least!
0
Bhaal85
Badges: 9
Rep:
?
#18
Report 17 years ago
#18
I would answer, but I'm off to bed. Night all.
0
Juwel
Badges: 18
Rep:
?
#19
Report 17 years ago
#19
(Original post by Bhaal85)
I would answer, but I'm off to bed. Night all.
<the no-vavavoom face> Dude you said that an hour ago.
Oh well I'm off too. See y'all tomorrow!
0
X
new posts
Back
to top
Latest
My Feed

See more of what you like on
The Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

Personalise

Following the government's announcement, do you think you will be awarded a fair grade this year?

Yes (536)
51.1%
No (513)
48.9%

Watched Threads

View All
Latest
My Feed

See more of what you like on
The Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

Personalise